IDENTIFIKASI KOMPONEN KIMIA ASAP CAIR TEMPURUNG KELAPA DARI WILAYAH ANYER BANTEN - Jayanudin .; Endang Suhendi (Jurnal Agroekoteknologi, 2012)
Liquid smoke is the vinegar of biomass pyrolysis process. Cellulose, hemicelluloses and lignin would be degraded into phenol compounds, carbonyls and organic acids that serves as a flavor enhancer and as an antifungal and antibacterial. The purpose of this study was to determine the chemical components in the liquid smoke from Anyer Banten region. This study is divided into two phases, namely phase pyrolysis of coconut shells at 300oC, 400oC and 500oC, pyrolysis time is 2, 3 and 4 hours, and coconut shell size 6-10 mm, 4-6 mm, and 1.6 - 4 mm. This stage produces dark red liquid, so do the second stage distillations process to obtain a pure liquid smoke. Liquid smoke with the greatest yield was analyzed using gas chromatography mass spectrometry (GCMS) QP.2010S Shimadzu. Based on the results of the study there were 11 chemical components were identified, the largest component is 46.56% acetic acid and phenol at 12.93%.Keywords: Liquid smoke, coconut shell, pyrolysis, acetic acid, phenol